Oviposition habitat selection by container‐dwelling mosquitoes: responses to cues of larval and detritus abundances in the field. (April 2014) - FADER, JOSEPH E.; JULIANO, STEVEN A.
<x xml:space="preserve">Abstract</x> Insects' oviposition responses to resource and larval densities can be important factors determining distributions and competitive interactions of larvae. Aedes albopictus (Skuse) and Aedes aegypti (L.) (Diptera: Culicidae) show aggregated distributions of larvae in the field, larval interactions that are affected by detritus resources, and oviposition responses to resource and density cues in the laboratory. In this study, field experiments were conducted to test whether these species choose oviposition sites in response to chemical cues indicating detritus resource quantity and quality or larval abundances. In Experiment 1, both species showed interactive responses to water conditioned with high or low quantities of senescent live oak leaves and density combinations of A. albopictus and A. aegypti larvae. Aedes aegypti preferred high‐detritus containers when conspecifics were absent. Aedes albopictus tended to prefer high‐detritus containers when larval density was low. We found no evidence of interspecific differences in oviposition preferences. In Experiment 2, A. albopictus preferred high detritus to low or no detritus, and rapidly decaying, high‐quality detritus to low‐quality detritus. Oviposition choices by these Aedes are mainly determined by resource quantity and quality, with larval densities having minor, variable effects. Oviposition responses of these species are unlikely to lead to resource partitioning. Aggregated distributions of these species in the field are unlikely to be products of oviposition choices based on larval densities.